Front Cover: Facile Synthesis of Large Wrinkled Gold Nanoparticles Using Anthracene‐Terminated Tripodal Amine Ligand and their Catalytic Efficiency (Eur. J. Inorg. Chem. 48/2020). Issue 48 (11th November 2020) - Devi, Manisha; Dhir, Abhimanew; Pradeep, Chullikkattil P.
Abstract : The Front Cover shows the use of an anthracene based tripodal amine as a capping ligand in the generation of small gold nanoparticles (AuNPs) in the presence of Au 3+ and ascorbic acid. These AuNPs agglomerate over time into large spherical AuNPs of size 300–400 nm with interesting wrinkled surface morphology. These wrinkled AuNPs exhibited enhanced activity in the catalytic reduction of 4‐nitrophenol compared to that of smooth surfaced AuNPs, probably because of their increased surface area. More information can be found in the Full Paper by C. P. Pradeep et al.